Building on the Archives: Connecting the CN/CO Intensity Ratio with Global Galaxy Properties in Nearby U/LIRGs - Blake Ledger; Christine D. Wilson; Osvald Klimi; Núria Torres-Albà; Toshiki Saito (The Astrophysical Journal)
We use the CN/CO intensity ratio to obtain the dense gas fraction, f _dense , for a sample of 16 ultraluminous and luminous infrared (IR) galaxies and compare f _dense with a suite of global galaxy properties. We find a significant correlation between f _dense and star formation rate calculated using both IR luminosities and radio continuum, although there is significant scatter in each relation. We find no trend between global or peak f _dense and merger stage. We find no correlation between global f _dense and X-ray luminosity; however, the correlation becomes significant when we measure f _dense at the location of peak X-ray emission. Our interpretation is that the dense gas is co-localized with strong X-ray emission from active galactic nuclei or strong central star formation.